2018
DOI: 10.1167/18.7.2
|View full text |Cite
|
Sign up to set email alerts
|

Attention alters spatial resolution by modulating second-order processing

Abstract: Endogenous and exogenous visuospatial attention both alter spatial resolution, but they operate via distinct mechanisms. In texture segmentation tasks, exogenous attention inflexibly increases resolution even when detrimental for the task at hand and does so by modulating second-order processing. Endogenous attention is more flexible and modulates resolution to benefit performance according to task demands, but it is unknown whether it also operates at the second-order level. To answer this question, we measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
62
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
2

Relationship

5
2

Authors

Journals

citations
Cited by 22 publications
(68 citation statements)
references
References 65 publications
(128 reference statements)
6
62
0
Order By: Relevance
“…On the other half of trials, a 100% Valid precue was displayed consisting of a white integer (0-3) and a single line to the right or left of the number. Similar to previous studies (Barbot & Carrasco, 2017;Jigo & Carrasco, 2018;Yeshurun, Montagna, et al, 2008), the line indicated which hemifield the target would appear and the number indicated the target's eccentricity: 0 represented the fovea and 1 through 3 indicated eccentric locations 3°, 6°, and 12°respectively. For foveal targets, no lines were presented with the Valid precue.…”
Section: Endogenous Attention Conditionmentioning
confidence: 58%
See 3 more Smart Citations
“…On the other half of trials, a 100% Valid precue was displayed consisting of a white integer (0-3) and a single line to the right or left of the number. Similar to previous studies (Barbot & Carrasco, 2017;Jigo & Carrasco, 2018;Yeshurun, Montagna, et al, 2008), the line indicated which hemifield the target would appear and the number indicated the target's eccentricity: 0 represented the fovea and 1 through 3 indicated eccentric locations 3°, 6°, and 12°respectively. For foveal targets, no lines were presented with the Valid precue.…”
Section: Endogenous Attention Conditionmentioning
confidence: 58%
“…The perceptual consequences of exogenous attention's automaticity have been demonstrated in texture segmentation tasks, which are constrained by spatial resolution (for reviews see, Anton-Erxleben & Carrasco, 2013 ; Carrasco & Barbot, 2014 ; Carrasco & Yeshurun, 2009 ). In these tasks, directing exogenous attention leads to an automatic increase in spatial resolution that improves performance for targets in the periphery where resolution is low but impairs performance near the fovea where resolution is already too high for the target ( Carrasco et al, 2006 ; Jigo & Carrasco, 2018 ; Talgar & Carrasco, 2002 ; Yeshurun, Montagna, et al, 2008 ; Yeshurun & Carrasco, 1998 ; Yeshurun & Carrasco, 2000 ). These impairments caused by valid exogenous cues are unique to texture segmentation tasks, which are characterized by a central performance drop, and have been attributed to an automatic and specific enhancement of contrast sensitivity to high SFs ( Carrasco et al, 2006 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our findings also relate to texture segmentation tasks, in which performance is constrained by the spatial resolution of the visual system and the scale of the texture target: Performance peaks at mid-eccentricity, where resolution is optimal for the scale of the texture target, and drops at more peripheral locations where resolution is too low and at more foveal locations where resolution is too high (Barbot & Carrasco, 2017;Carrasco & Barbot, 2014;Carrasco, Loula & Ho, 2006;Gurnsey, Pearson & Day, 1996;Jigo & Carrasco, 2018;Morikawa, 2000;Talgar & Carrasco, 2002;Yeshurun & Carrasco, 1998, 2000Yeshurun, Montagna & Carrasco, 2008). Modulating the contribution of either high SFs or low SFs affects texture-segmentation performance in a manner consistent with resolution changes: selectively removing high SFs from the stimulus display eliminates the CPD (Morikawa, 2000).…”
Section: Discussionmentioning
confidence: 71%